THE INVOLVEMENT OF THE SPORTS MEDICINE SPECIALIST IN THE MENTAL TRAINING OF PROFESSIONAL ATHLETES - Drosescu P. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
The achievements of professional athlete should be supported by an inter-disciplinary team; aside from the main actors (athlete and coach), it is also necessary to have the involvement of: a sports medicine specialist, a massage therapist, a physical trainer, a psychologist, a nutritionist, a medical assistant and a manager. For financial reasons, this technical staff is not found alongside professional athletes (at least in Romania), thus most of the times the tasks are being handled by the coach, sports medicine specialist or massage therapist. The Sports Medicine specialist, through the training they have received, can bring a contribution to the psychological training of athletes - within certain limits and without interfering with the area of Psychology if they do not have training in this area. In the present article, we wish to present a few of the possibilities available to the Sports Medicine specialist and the ways this can be accomplished. The information presented here is the result of the author's 15 years' experience in this field.